Masthead (VERUM: Journal of Scientific Initiation, 2025)
EDITORIAL TEAMEDITOR-IN-CHIEFMe. Ewerton da Silva Ferreira, Center for Interdisciplinary Studies, BrazilJUNIOR EDITORMaster’s Student Eduardo Lima, Federal University of Santa Catarina, BrazilTECHNICAL SUPPORTBachelor Ricardo Macuglia, Center for Interdisciplinary Studies, BrazilMe. Tiara Cristiana Pimentel dos Santos, University of Passo Fundo, BrazilBachelor Maria Fernanda Coffi Ávila, Federal University of Pampa, BrazilEDITORIAL BOARDDr. Alan Dutra Melo – Federal University of Pampa, BrazilDr. Cristóvão Domingos de Almeida – Federal University of Mato Grosso, BrazilDr. Darlan De Mamann Marchi – Federal University of Pelotas, BrazilDr. Juliani Borchardt da Silva – Federal University of the Southern Border, BrazilDr. Léia Teixeira Lacerda – State University of Mato Grosso do Sul, BrazilDr. Rogério Piva da Silva – Federal University of Rio Grande, BrazilDr. Taniamara Vizzotto Chaves – Farroupilha Federal Institute of Education, Science and Technology, BrazilCOVER DESIGNEduardo Lima, Federal University of Santa Catarina, BrazilABOUT THE JOURNALVERUM: Journal of Scientific Initiation aims primarily to disseminate articles authored by undergraduate students alongside their academic advisors, especially those linked to scientific initiation programs. In doing so, it fosters exchanges between authors and readers to advance knowledge across various fields. VERUM publishes works stemming from the triad of Teaching, Research, and Extension on a rolling basis.Se quiser também a versão em espanhol, posso providenciar na sequência! Deseja isso?
Keywords: Masthead; Interdisciplinary